Weighing in on the Off-Label Use: Initial Experience of Neuroform EZ Stenting for Intracranial Arterial Stenosis in 45 Patients - Du, Zhihua; Mang, Jing; Yu, Shengyuan; Tian, Chenglin; Cao, Xiangyu; Liu, Xinfeng; Ma, Renzheng; Zhang, Rongju; Lv, Bin; Wang, Jun (Frontiers in Neurology, 2018)
Background: The role of stenting for intracranial arterial stenosis (ICAS) has been increasingly debated due to negative results of randomized trials. Thus, exploration of more appropriate devices may hopefully shed light on the endovascular approach, especially for patients with recalcitrant ICAS related to a high risk of stroke. We sought to present and analyze the data of Neuroform EZ stenting for medically refractory ICAS in a single-center series. Materials and methods: Between November 2016 and January 2018, 45 consecutive patients treated with the Neuroform EZ stent were included in our retrospective study. Outcomes evaluation included successful procedure rate, vascular event within 30 days and recurrent stenosis for at least 6 months after the procedure. Results: The technical success rate was 100% for all 46 stenotic lesions. Mean pre-stent stenosis was 86.5 ± 8.7%, improving to 23.7 ± 18.1% after stenting. Combined procedure related vascular event rate was 2.2% (n =1) within 30 days after the procedure. No in-stent restenosis was observed during an average follow-up period of 7.3 months. Conclusion: The Neuroform EZ stent system could serve as an off-label but promising optional device for ICAS stenting in carefully selected subgroup of patients. Further longer term clinical follow-up is mandatory to validate our initial results.